Exploration of older prisoner's social needs, who attended one of two prison initiatives for older people: an inductive phenomenological study. Issue 2 (13th August 2020) - Brooke, Joanne; Rybacka, Monika
Abstract : Purpose: The purpose of this study was to explore the social needs and experiences of older prisoners who were attending one of two social initiatives in a prison in England. Design/methodology/approach: This paper is based on an interpretative phenomenological study, conducted in a prison in the South West of England. Older prisoners attending an initiative implemented for those over 55, a purposive activity or a social task group, participated in focus groups, which were audio recorded and thematically analysed. Findings: Two overarching themes were identified. Firstly, the need to feel safe: prisoners felt attending an initiative provided them with a safe haven away from noisy and boisterous younger prisoners, who they perceived as different from them and who received preferential treatment. Secondly, being provided with a purpose: prisoners felt they belonged among their peers, which motivated them to attend and support group activities. Research limitations/implications: This study was completed in one prison. However, both initiatives supported the social needs of older prisoners and enabled them to leave their cells, although they felt unsafe when not attending an initiative. Originality/value: There remains a need to support the process of integrating younger and older prisoners, by the provision of both integrated and separate initiatives, with the aim of developing cross-generational and bi-directional peer support.